Plataforma Rumo: um ambiente interativo para aprendizagem baseada em projetos no ensino superior - OLIVEIRA, Fransuze dos Santos (Universidade Federal do Pará, 2021)
This work aimed to design a prototype of an interactive platform that facilitates the use of the Project Based Learning (ABPj) approach in higher education. As theoretical references, we are based on studies and reflections on conceptions and principles of Project-Based Learning, Active, Meaningful and Collaborative Learning, theories about the construction of knowledge from experience, interaction with others and with the world, the autonomy of the educating, throughout its metacognition process. For the construction of the prototype, qualitative research was carried out, with the creation of instruments and workshops to build the product's functionalities. Among the most relevant points are the understanding of the applicability of the ABPj approach, the critical points from the perspective of teachers and students and which are the most important functionalities, in addition to the construction of specific tools for planning and monitoring the approach. Another important point was the realization of courses on the ABPj approach to enable its understanding and application in a clear way, with the visualization of a step by step and, thus, the systematization of teaching from the approach in question. As a result of the research, it was possible to obtain a) the identification of critical points for the application of the ABPj approach; b) the systematization of teaching and assessment planning in the ABPj approach; c) the construction of a platform prototype, including screens and functionalities, which, as an interactive tool, contemplates the systematization of the previous item. The main conclusions are: a) the application ABPj, as a teaching and assessment approach, requires a clear understanding of teachers and students and, therefore, the organization of the teaching-learning process is fundamental; b) the platform as a digital tool will allow data collection that will serve as a basis for countless analyzes, making the teaching, evaluation and learning process a living system in constant improvement based on the identification of the results of previous practices.